Temperature Effect on Lorentz Line Widths within the Carbon Dioxide Band - Al-Ibadi, Zeyad (Academia Open, 2026)
General Background Carbon dioxide drives global climate change, requiring highly precise satellite spectral retrievals. Specific Background The fundamental 4.2–4.3 µm band is essential for column retrievals where collisional broadening dominates. Knowledge Gap Yet, systematic recomputation of temperature-dependent Lorentz widths and database consistency across atmospheric temperatures remains unverified. Aims This study evaluates temperature effects on Lorentz widths for 2,370 lines (2325–2380 cm⁻¹) in HITRAN2020 from 200 K to 400 K. Results Band-averaged widths decrease 39.2% (0.0901 to 0.0548 cm⁻¹) with exponents centering at 0.71, showing tighter constraints for strong lines over weak transitions. Novelty This work provides the first systematic database consistency verification of 4.3 µm band parameters using non-linear power-law fitting. Implications Omitting temperature-dependent adjustments causes systematic modeling errors up to 46%, proving radiative transfer codes must implement database exponents to ensure reliable retrievals. Keywords : Carbon Dioxide, Lorentz Broadening, Temperature Dependence, Spectroscopic Database, Line Shape Key Findings Highlights A 39.2% monotonic reduction in average Lorentz half-width occurs between 200 K and 400 K. The re-determined temperature exponents show high database self-consistency with a mean value of 0.71. Strong transitions exhibit minimal parameter scatter and provide greater reliability than weak spectral lines.